Manajemen Kurikulum Dan Pengembangan Pengajaran, Penelitian Serta Pengembangan Pendidikan Yang Berkualitas - Suwarni, Suwarni; Bendriyanti, Rita Prima; Asnawati, Asnawati; Astuty, Lina Tri; Perdima, Feby Elra; Dina, Dina; Astuti, Reni (Jurnal Dehasen Untuk Negeri, 2025)
This report describes the results of community service activities carried out by Dehasen University Bengkulu with the title ‘Curriculum Management and Development of Quality Teaching, Research, and Education Development at SMA 8 Bengkulu City.’ This activity aims to improve the quality of education at SMA 8 Bengkulu City by focusing on strengthening curriculum management, developing innovative teaching methods, and encouraging a culture of research among teaching staff. During the activity, the needs of the school were identified, followed by the organisation of workshops and training for teachers. The materials presented included the preparation of a competency-based curriculum, the application of creative learning methods, and the use of effective evaluation techniques. In addition, teachers were also given an understanding of the importance of classroom action research (PTK) to improve the quality of learning. The results of this activity show an improvement in the preparation of a more structured and competency-based curriculum, as well as the application of learning methods that are more innovative and in accordance with student needs. Teachers are also more open to the practice of research as a means to improve and develop the learning process. Despite several obstacles, such as time constraints and the diverse abilities of the participants, this activity succeeded in having a significant and beneficial impact on improving the quality of education at SMA 8 Bengkulu City.